Major target for UV-induced complete loss of HIV-1 infectivity: A model study of single-stranded RNA enveloped viruses - Koma, Takaaki; Doi, Naoya; Suzuki, Akihiro; Nagamatsu, Kentaro; Yasui, Takeshi; Yasutomo, Koji; Adachi, Akio; Minamikawa, Takeo; Nomaguchi, Masako (Frontiers in Virology, 2022)
Deep ultraviolet light (UV) is useful for the disinfection of microorganisms, including bacteria and viruses. Although genome damage by UV has been widely accepted, the adverse effects of UV on the activity and/or function of viral proteins including the envelope components are poorly documented. Worthy of note, the observed unfavorable UV-effects for viruses are only insufficiently analyzed in association with the reduction in viral infectivity. In this study, we aimed to clarify which component of virions affected by UV significantly correlates with the loss of viral infectivity using HIV-1 as a model for single-stranded RNA enveloped viruses. Using our UV irradiation apparatus at three wavelengths (265, 280, and 300 nm), we first quantitatively determined the UV power density and irradiation period of each wavelength required for a reduction in infectivity. A heat-treated sample as a control drastically reduced the virion-associated reverse transcriptase (RT) activity and Gag-p24 level. The UV-irradiated samples at the three wavelengths, completely lacking viral infectivity, showed p24 levels similar to those without irradiation. While the virion-associated RT activity was gradually decreased in a wavelength and power density dependent manner, this reduction did not explain the loss of viral infectivity by UV. Remarkably, virological assays revealed that the entry efficiency of the UV-irradiated virus samples at the three wavelengths is comparable to those without irradiation. Importantly, this result shows that, even the virions exposed to UV of various wavelengths at the lethal level, still maintain the function of their envelope composed of a host lipid bilayer and viral proteins. In sharp contrast, UV-induced genome damage shown by semiquantitative RT-PCR correlated well with the reduction in viral infectivity, indicating that it is a major determinant for virus inactivation by UV. The degree of damage was found to be distinct among the regions analyzed. This was probably due to the different nucleotide sequences in those genomic regions amplified by PCR. Our data clearly demonstrate a principal mechanism for viral inactivation by UV and provide information contributing to the improvement of UV-based disinfection technology for microorganisms.